2008
DOI: 10.1177/1054773808324651
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Upper Arm and Forearm Blood Pressure

Abstract: The upper arm is the primary site used to obtain a blood pressure measurement (BPM); however, when it is not possible to use the upper arm, the forearm is a commonly used alternate site. This study determines if there is a significant difference between upper arm and forearm BPMs among adults and examines the relationship of participant characteristics to the BPM difference. A convenience sample was recruited from a low-income, independent-living, 104-apartment complex in the Midwest. Of the 106 participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…[9][10][11][12][13]19 Although these studies were based on NIBP measurements alone, our results show a similar trend toward forearm overestimation. In our study, the NIBP measurements taken on the upper arm showed a tendency toward underestimating ABP.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…[9][10][11][12][13]19 Although these studies were based on NIBP measurements alone, our results show a similar trend toward forearm overestimation. In our study, the NIBP measurements taken on the upper arm showed a tendency toward underestimating ABP.…”
Section: Discussionsupporting
confidence: 57%
“…Nevertheless, studies validating BP cuff placement on the forearm vs the upper arm provide little information relating to obese participants or specific body mass index (BMI) measurements. [9][10][11][12][13] The purpose of our study was to determine the accuracy of oscillometric NIBP measurements, using cuffs at different locations and with various wrapping techniques, compared with intra-arterial measurements in obese patients undergoing surgery.…”
Section: Résumémentioning
confidence: 99%
“…In 2 studies, 11,13 cuff types were compared (standard vs large, rigid cylindrical vs conical); in 3 studies, 4,17,21 blood pressure measurements obtained via direct intra-arterial vs ausculatory/oscillometric techniques were compared; and in 6 studies, [14][15][16][18][19][20] blood pressure measurements obtained from the upper arm versus the forearm were compared.…”
Section: Resultsmentioning
confidence: 99%
“…7,8,18 When assessing blood pressure at alternative locations, it is essential to recognize that blood pressure varies appreciably in different parts of the arterial system, with SBP increasing in more distal arteries and DBP decreasinig. 23 Thus, because measurements of blood pressure in the forearm generally yield overestimates of SBP, DBP, and mean arterial pressure (MAP) compared with the upper arm (reported variances, 2.3-27 mm Hg), 10,14,[19][20][21]24,25 it is important to decide what discrepancy is clinically acceptable. 10,14,20 As McFarlane 10 described, a difference of ±5 mm Hg (standard deviation ≤8 mm Hg) is the standard used by the International Standards Organization and manufacturers that test noninvasive devices for measuring blood pressure against mercury sphygmo manometers.…”
Section: Mcfarlanementioning
confidence: 99%
“…In a majority of studies, recruiting young healthy adults and eliminating individual characteristics that might influence blood pressure measurements, such as known cardiac arrhythmias or unstable medical condition, controlled sample selection. [40][41][42][43][44] Pierin and colleagues, 42 Vinyoles and colleagues, 45 Schell and colleagues, 43,44,46,47 Domiano and colleagues, 48 and Leblanc and colleagues 49 reported participants classified as obese as defined by a BMI greater than 30 kg/m 2 ; however, only 1 study 49 reported participants classified as morbidly obese separately. In 2 studies 42,49 in which obesity was required for inclusion in the sample, comparison of the conclusions with individuals who are classified as normal weight is not attainable.…”
Section: Literature Analysismentioning
confidence: 99%